Solve using the Square Root Property x^2-10x+25=0

Math
x2-10x+25=0
Factor using the perfect square rule.
Tap for more steps…
Rewrite 25 as 52.
x2-10x+52=0
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab=2⋅x⋅-5
Simplify.
2ab=-10x
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=x and b=-5.
(x-5)2=0
(x-5)2=0
Set the x-5 equal to 0.
x-5=0
Add 5 to both sides of the equation.
x=5
Solve using the Square Root Property x^2-10x+25=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top